Embedment of Montgomery Algorithm on Elliptic Curve Cryptography over RSA Public Key Cryptography. (2016) - Thomas, Aswathi; Manuel, Ebin M.
Abstract: The Elliptic Curve cryptosystem has replaced the prevailing first generation public key algorithms – RSA and Diffie - Hellman due to its shorter key size requirement. This paper presents a modified Elliptic Curve and RSA cryptosystem by incorporating a newly designed Montgomery multiplier algorithm for better efficiency. The inherent disadvantage of delay due to the large number of computations in Elliptic Curve cryptography is improved substantially by the implantation of the modified Montgomery algorithm in it. The simulation results show significant improvement in terms of speed and power.